PRODUKSI BIOETHANOL DARI RUMPUT GAJAH SECARA KIMIA - Sari, Ni Ketut (Jurnal Teknik Kimia, 2009)
Availability of bulrush can be obtained by continue and abundance, representing one the less exploited crop.Bulrush only used as livestock food, sometimes bulrush also considered to be intruder crop. But bulrush have cellulose rate, glucose, extract able to be used as one the ethanol producer materials. Obtained Ethanol rate from study produce bio ethanol from bulrush between 23-28 %, to increase purity of ethanol rate conducted bydissociation use batch distillation. Research produces bio ethanol from bulrush chemically to look for bio ethanol alternative raw material and study sour hydrolysis process and fermentation. In research produce bio ethanol from bulrush chemically to process hydrolysis at condition remains to: temperature 30oC, water 7 liters,hydrolysis time 1hour and condition change: bulrush weight 50, 100, 150, 200, 250, 300 (gram), HCL condensation volume 10, 20, 30, 40, 50(ml). Is then continued by fermentation process at condition remain to:temperature 30oC, pH 4.5; fermentation volume 500 ml and condition change: fermentation time 4, 5, 6, 7, 8(day), starter 8 %, 10 %, 12 %. From research produces bio ethanol from bulrush chemically obtained [by] result, [at] best glucose rate hydrolysis process 26.29 %, bulrush weight 200 gram. At best condition ferment process use saccharomyces cerevisiae starter 10 % during 6 day, yielding ethanol equal to 27.71 % and glucose rate is rest of 8.09 %. To obtain get purity ethanol product to process separation of continuation with batch distillation, after conducted separation continue to be obtained ethanol rate (90-95) %. From result is obtained that is ethanol rate (90-95) %, bulrush can be used as alternative raw material making of bio ethanol. But for the standard of bio ethanol that is ethanol rate above 98 %, so that require to furthermore process.  Keyword: bio ethanol, fermentation, hydrolysis, purification, bulrush